Ta có: x 2 − 3 x = 0 ⇔ x = 0 x = 3
Do đó, tập nghiệm của phương trình đã cho là S 0 = 0 ; 3 .
Xét các đáp án:
- Đáp án A. Ta có: x 2 + x − 2 = 3 x + x − 2
⇔ x − 2 ≥ 0 x 2 − 3 x = 0 ⇔ x ≥ 2 x = 0 x = 3 ⇔ x = 3
Do đó, tập nghiệm của phương trình là S 1 = 3 ≠ S 0
- Đáp án B. Ta có: x 2 + 1 x − 3 = 3 x + 1 x − 3 ⇔ x − 3 ≠ 0 x 2 − 3 x = 0 ⇔ x = 0
Do đó, tập nghiệm của phương trình là S 2 = 0 ≠ S 0 .
- Đáp án C. Ta có
x 2 x − 3 = 3 x x − 3 ⇔ x − 3 ≥ 0 x 2 − 3 x = 0 x − 3 = 0 ⇔ x ≥ 3 x = 0 x = 3 ⇔ x = 3
Do đó, tập nghiệm của phương trình là S 3 = 3 ≠ S 0 .
- Đáp án D. Ta có: x 2 + x 2 + 1 = 3 x + x 2 + 1 ⇔ x 2 = 3 x ⇔ x = 0 x = 3
Do đó, tập nghiệm của phương trình là S 4 = 0 ; 3 ≠ S 0 .
Đáp án cần chọn là: D